Environmental acoustics - Doelle, Leslie L. (New York : McGraw Hill Education, 1972)
This book is divided into four parts. Part I introduces the subject and discusses important terms. Part II covers room (or space) acoustics, that is, the acoustical design of auditoriums, such as lecture halls, theaters, concert halls, opera houses, motion-picture theaters, churches, sound studios, and open-air theaters. Part III discusses various aspects and methods of environmental noise control, including sound-insulating walls, floors, doors, windows, and the noise control of auditoriums, residential buildings, hotels, motels, schools, hospitals, offices, and industrial buildings. Part IV is concerned with the execution supervision, and checking of acoustical works.
Part 1. Introduction -- 1. Environmental acoustics in architectural design -- 2. A brief of acoustical ideas -- 3. Properties of sound -- Part 2. Room (or Space) Acoustics -- 4. Acoustical phenomena in enclosed spaces -- 5. Sound-absorbing materials and constructions -- 6. Acoustical requirements in auditorium design -- 7. Acoustical design of rooms for speech -- 8. Acoustical design of rooms for music -- 9. Places of assembly with mixed acoustical requirements -- 10. Acoustical design of studios -- 11. Sound-amplification systems -- 12. Acoustical correction of existing auditoriums -- Part III. Environmental Noise Control -- 13. Introduction to environmental noise control -- 14. Sound-insulating construction -- 15. Noise criteria -- 16. Control of mechanical noise and vibration -- 17. Noise control in specific types of buildings -- Part Four: Execution -- 18. Detailing, specification and supervision -- 19. Checking the acoustical performance of auditoriums -- Appendix A. Sound absorption coefficients -- Appendix B. Sound-insulation values of walls -- Appendix C. Sound-insulation values of floors -- Appendix D. -- General bibliography.
Includes bibliographical references and index.
Keywords: ARCHITECTURAL ACOUSTICS